HUME’S EXPERIMENTAL SCIENCE ON HUMAN NATURE IN THE TREATISE - Grzelinski, A. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The aim of the paper is to present the meaning of the notion of «experimental method», which is mentioned in the title of David Hume’s Treatise of Human Nature. I claim it to be the ground of the whole system of Hume’s system of sciences concerning various aspects of human life.